The Influence of Internal and External Factors on Arabic Language Learning Interest among Arabic Language Education Students - Amanda, Chikanti; Khan, Junaid (Journal of Arabic Language Learning and Teaching (JALLT), 2024)
Arabic language learning in the Arabic Language Education program at State Islamic University Sultan Aji Muhammad Idris Samarinda faces diverse challenges due to varying student interests. Interest, defined as attention and pleasure towards learning, is influenced by internal and external factors. The study aimed to assess these factors' impact on student interest. Employing quantitative methods, the research used multiple linear regression analysis on a sample of 75 third-semester students, utilizing observation, interviews, surveys, questionnaires, and documentation. Results revealed significant positive influence of internal factors on student interest (t-value = 3.385 > 1.993), while external factors exhibited significant, partially positive impact (t-value = -2.294 > 0.432) with some negative effects. Findings emphasize the need for students to recalibrate their intent and determination in Arabic language learning. They should also address external influences to maintain interest during their academic journey.